Null Hypothesis Significance Testing: a short tutorial - Pernet,Cyril R (PeerJ PrePrints, 2015)
Although thoroughly criticized, null hypothesis significance testing is the statistical method of choice in biological, biomedical and social sciences to investigate if an effect is likely. In this short tutorial, I first summarize the concepts behind the method while pointing to common interpretation errors. I then present the related concepts of confidence intervals, effect size, and Bayesian factor, and discuss what should be reported in which context. The goal is to clarify concepts, present statistical issues that researchers face using the NHST framework and highlight good practices.
Keywords: NHST; p-value; confidence intervals; effect size; reporting